Genetic diversity and lack of molecular evidence for hemoplasma cross-species transmission between wild and synanthropic mammals from Central-Western Brazil - Gonçalves, Luiz Ricardo [UNESP]; Herrera, Heitor Miraglia; Nantes, Wesley Arruda Gimenes; Santos, Filipe Martins; Porfírio, Grasiela Edith de Oliveira; Barreto, Wanessa Teixeira Gomes; de Macedo, Gabriel Carvalho; Assis, Willian de Oliveira; Campos, João Bosco Vilela; da Silva, Thiago Merighi Vieira [UNESP]; Mariano, Leticia Colovatti [UNESP]; Barros-Battesti, Darci Moraes [UNESP]; et al. (Elsevier, 2020)
Globally, hemotropic mycoplasmas (hemoplasmas) comprise an emerging or remerging bacteria group that attaches to red blood cells of several mammal's species and in some cases, causing hemolytic anemia. Herein, we assessed the occurrence, genetic diversity, the factors coupled to mammals infection, and the phylogeographic distribution of hemoplasmas in sylvatic and synanthropic mammals and their associated ectoparasites from Brazil. We collected spleen and/or blood samples from synanthropic rodents (Rattus rattus [N = 39] and Mus musculus [N = 9]), sylvatic rodents (Hydrochoerus hydrochaeris [N = 14]) and opossums (Didelphis albiventris [N = 43]). In addition, ticks (Amblyomma spp. [N = 270] and lice (Polyplax spinulosa [N = 6]) specimens were also sampled. Using a PCR targeting the 16S rRNA region, out of 48 small rodents, 14 capybaras and 43 opossums DNA samples, hemoplasma DNA was found in 25%, 50%, and 32.5% animals, respectively. Besides, we reported hemoplasma DNA in Amblyomma sp. (22.2% [2/9]) and lice (100% [2/2]) pools samples from rats, and one female A. sculptum DNA sample (3% [1/33]) obtained from a capybara. Additionally, and in agreement with ML analysis, the network analyses showed a clear phylogenetic separation among the hemoplasmas genotypes found in the different host species sampled, thus, suggesting the absence of cross-species hemoplasmas transmission between the mammals trapped. Finally, using the NTC network analysis, we reported the same 16S rRNA Mycoplasma genotype circulating in Rattus sampled in Brazil, Hungary, and Japan.
Keywords: Capybaras; Hemotropic mycoplasmas; Lice; Opossum; Phylogenetic analysis; Rattus rattus and Ticks